41. CURRENT SITUATION AND SOME FACTORS AFFECTING DIGITAL HEALTH TRANSFORMATION AT COMMUNE HEALTH STATIONS: A QUALITATIVE STUDY (Vietnam Journal of Community Medicine, 2025)
Digital transformation is an inevitable trend today in the world as well as in our country in all areas of social life, including the health sector, especially at commune health stations, which directly take care of people's health. Commune health stations have been active and proactive in digital transformation of health activities in recent times and have achieved initial results: having a full legal basis for applying information technology according to the Government’s project 06/CP, 100% of communes have 2 or more computers, 100% of communes have deployed software to implement 18 health programs, 100% of communes are connected to the software of the health insurance, but there are still 6 following limitations (6 no’s): 1. Not synchronous information technology infrastructure, 2. Not synchronous software, 3. Not synchronous health information system (HIS), 4. Not connecting medical data, 5. Not unified medical terminology for computers, 6. Not enough knowledge and practical skills to apply software in professional activities of health staff at commune stations in district H, province T. The topic has identified a number of factors affecting digital transformation at the stations commune health.
Keywords: Digital transformation of health; commune health station; influencing factors